Philosophy as Descartes found it practice and theory - Copenhaver, Brian P. 1942- (Oxford University Press, 2024)
What was philosophy as Descartes found it around 1620? What was philosophy like before Descartes reformed it after 1637? What features of philosophy did he want to fix, and what tools did he use? To answer such questions, how should philosophers do their work today? One answer is surprising: that Descartes wrote picture books, for example. Another is challenging: that philosophers in the present would be better students of their discipline's past if they spent less time on past philosophy as they commonly understand it. The change would be transformative. But big changes have happened in philosophy's past for non-philosophical reasons that need attention from philosophers today, when oblivion has impeded their study of such changes. Attending to understudied causes of philosophical effects will show philosophers how to repair the damage that oblivion has done to their work. Mending stories about philosophy begins in this book with Descartes and his predecessors...mostly the predecessors...on meditation and method. Brian Copenhaver examines these familiar topics from a neglected point of view before introducing a different and unfamiliar Descartes: the author of the Discourse and Meditations as a writer of picture books. Three chapters about these topics...meditation, method, and picturing...are the practice justified by two theoretical chapters, one about how philosophy changes, the other about the oblivion that cancels memories of change